"From Heroes to Zeroes" – self-initiated expatriation of talented young footballers. Issue 2 (12th June 2017) - Egilsson, Birnir; Dolles, Harald
Abstract : Purpose: The sports industry is a forerunner in the international quest for talent as the search by sport clubs and the corresponding self-initiated expatriation of athletes starts at a very early age. The purpose of this paper is to address this phenomenon by exploring the experiences of talented young Icelandic footballers (soccer players) in their transition from Iceland into senior-level professional football in European leagues across six dimensions – three individual and three cultural. Design/methodology/approach: Biographical narrative interviews have been conducted with eight Icelandic players moving overseas at a young age with the purpose of advancing their career. To investigate the coping strategies applied, a purposeful sampling approach was chosen, given that half of the participants successfully dealt with transitions in their career, while the other half did not experience the same success. Findings: As an overall result, the expatriate journey for young footballers is complex, influenced by many events, expectations, conditions and pressures that affect their support web and ability to adjust. Reflecting on the experiences of successful transitions, problem-focused coping strategies have been more effective than emotion-focused coping. Research limitations/implications: This study highlights some necessary conditions and coping strategies for young self-initiated sports expatriates to cope with the expatriate transition successfully. Originality/value: The authors contribute to research on expatriation, as this specific group of "young professionals" has not yet been addressed by the research within international human resource management. Our research framework responds to calls in the literature to consider additional stages of player development and an array of individual and cultural factors that may have a significant role in shaping players' careers abroad.